Rural Economic Transformation: The Role and Potential of Village-Owned Enterprises in Building Local Independence in Kepunduhan Village, Tegal Regency - Aldinosa Oktrivargas; Mohammad Aulia Rachman (UPT Publikasi Ilmiah UNISBA, 2026)
Rural economic transformation is one of the important agendas in efforts to realize village prosperity and independence. One instrument that can be used to support this transformation is Village-Owned Enterprises (BUMDes). This research aims to explore the role and potential of BUMDes in transforming the rural economy, by taking a case study in Kepunduhan Village, Tegal Regency. This research uses a qualitative approach with a case study method, involving field observations, in-depth interviews and document study. The research results show that BUMDes in Kepunduhan Village have succeeded in optimizing local resource management through the development of business units such as trade, savings and loans, waste management, payment services, and carpentry/building rentals. The existence of BUMDes makes a significant contribution to improving the village economy, creating jobs and improving community welfare. The success of BUMDes in Kepunduhan Village is supported by active community involvement, community capacity development, as well as partnerships with related institutions, non-governmental organizations and the private sector. However, there are several challenges such as limited human resources, access to capital, and policy support that still need to be overcome. This research concludes that BUMDes have great potential in transforming the rural economy and building local independence, provided there is adequate policy support, active community involvement, and strong partnerships with various related parties.